PENERAPAN METODE KRITIK VIDEO UNTUK MENINGKATKAN HISTORICAL COMPREHENSION SISWA DALAM PEMBELAJARAN SEJARAH : PenelitianTindakanKelas di Kelas X IIS 2 SMAN 1 Cimahi) Skripsi - Tilawati, Illa (2015)
Skripsiiniberjudul "PenerapanMetodeKritik Video untukMeningkatkanHistorical ComprehensionSiswadalamPembelajaranSejarah (PenelitianTindakanKelas di Kelas X IIS 2 SMA Negeri 1 Cimahi)".Permasalahan yang dibahasdalamskripsiiniadalahmengenaipenerapanstrategipembelajaranaktifyaitumetodekritik video agar dapatmeningkatkanhistorical comprehensionsiswayaitusalahsatudarikemampuanhistorical thinking skills yang harusdikuasaisiswadalammempelajarisejarah.Hal inidilatarbelakangiolehpertama, rendahnyakemampuansiswadalammemahamimateri yang dipelajarinya yang ditandaidengantidakmampunyasiswadalammenguraikanjawabansecaralisandenganmenggunakan kata-katanyasendiriberdasarkanpemahamannya.Kedua, siswakurangdapatmengutarakanpertanyaanmaupunjawabanpadasaat guru menerangkanmaupunsaatdiskusidiadakan, sehinggasiswaterlihatbegitupasifselamapembelajaranberlangsung.Ketiga, siswakurangmampuuntukmenyimpulkansecaralisanmateri yang telahdibahasnya.Makapenelitimerumuskanpermasalahandalambeberapapertanyaanyaitu: 1) Bagaimanamerencanakanpembelajaransejarahdenganmenerapkanmetodekritik videountuk meningkatkanhistorical comprehensionsiswa? 2) Bagaimana guru melaksanakanpembelajaran sejarah dengan menerapkanmetodekritik video untuk meningkatkanhistorical comprehensionsiswa? 3) Bagaimanapeningkatanhistorical comprehensionsiswadalampembelajaransejarahdiKelassetelahditerapkannyametodekritik video? 4) Bagaimana upaya gunamengatasi kendala yang dihadapi dalam pembelajaran sejarah ketika diterapkannyametodekritik video untukmeningkatkanhistorical comprehensionsiswa?PenelitianinimenggunakanmetodepenelitiantindakankelasdengandesaindariKemmisdan Taggart dikarenakanpadapenelitianinipenelitiinginmeningkatkankemampuanhistorical comprehensionsiswa.Peningkatankemampuantersebutdiperlukanbeberapa kali tindakan yang berulang-ulang.DesainKemmisdan Taggart inimenggambarkantindakan-tindakan yang disusundalamsiklus-siklus yang cocokdigunakanuntukmeningkatkankemampuanhistorical comprehension.Tahapansetiapsiklusnyaberupaperencanaan (plan), tindakan (act), observasi (observe), danrefleksi (reflect). Selamapenelitianberlangsungpenelitimenggunakanbeberapateknikpengumpulan data yaituobservasi, wawancara, danstudidokumentasidenganbeberapainstrumenyaitulembarobservasi, pedomanwawancara, dancatatanlapangan.Berdasarkanhasildaripenelitianmenunjukkanbahwahistorical comprehensionsiswasecarakeseluruhanmengalamipeningkatanmeskipunterdapatbeberapakendalasehinggaterjadijugapenurunan.Penelitimemberikan saran kepadapenelitilain agar memilikipersiapan yang matangdalammenerapkanmetodeini, kepada guru agar memperkayalagipengetahuanmengenaiberbagaimetodedan media sehinggapembelajaranpunlebihberkualitasdanbermakna, kepadasiswa agar selalubelajaraktifdanmandiri, dankepadasekolah agar terusmengupayakanpeningkatankualitaspembelajaran. This paper entitled "The Use of Critic Video Method to Enhancing Student's Historical Comprehension in a History Subject (A Classroom Action Research of Tenth Grade Students IIS 2 in 1 Senior High School Cimahi)".The problem in this paper concerned about the application of an active learning strategy which was a critic video method. It was selected to increase students' historical comprehension since it was one of historical thinking skills that had to be acquired by the students in learning a history.This issue was motivated by, firstly, the low of the students' ability in understanding the materials they learn; it was characterized by the inability of the students in elaborating the answers verbally using their own words based on their understanding.Secondly, the students were less to utter the questions and the answers when the teacher was explaining or the discussion session was held, therefore, the students seemed passive during a learning process.Thirdly, the students' ability was less to sum up orally the material they had been discussed. So researcher formulated the problems in several questions; 1) How to plan the history learning by applying the critic video method to improve the students' historical comprehension?How does the teacher present the history by utilizing the critic video method to improve the students' historical comprehension? 3) How to enhance the students' historical comprehension in learning the history in the classroom after the critic video method is applied? 4) What efforts to overcome the obstacles which are faced in the history learning when the critic video method is applied to enhance the students' historical comprehension?This paper used an action research which was designed by Kemmis and Taggart since the research would like to improve the ability of the students' historical comprehension.Enhancing the ability required several times repeated measures. Kemmis and Taggart's design described actions that were arranged in cycles and suitable to be used to improve the students' historical comprehension.The steps of each cycle were plan, act, observe, and reflect. During the observation, the researcher utilized some techniques of collection data which were observation, interview, and documentation with some instruments; they were observation paper, interview guidelines, and field notes.Based on the result of the reseach, it showed that the students' historical comprehension increased overall even though the obstacles were exist, so the result decreased as well.The researcher give suggestions to the further researchers so that they have to be well-prepared in applying this method. The researcher also suggests the teacher to add more the knowledge of methods and media, in a result, the learning process can be more qualified and meaningful. For the students, study active and independent and for the school, continue to work on improving the quality of education.